Complication Rates After Total Hip and Knee Arthroplasty in Patients With Hepatitis C Compared With Matched Control Patients. Issue 12 (December 2017) - Cancienne, Jourdan M.; Kandahari, Adrese M.; Casp, Aaron; Novicoff, Wendy; Browne, James A.; Cui, Quanjun; Werner, Brian C.
Abstract : Background: A paucity of data exists regarding long-term outcomes among patients with hepatitis C who undergo total hip arthroplasty (THA) and total knee arthroplasty (TKA). Methods: We queried a database for patients with hepatitis C who underwent THA and TKA. We then identified their rates of several postoperative complications and compared them with the same rates among mutually exclusive matched control cohorts. Results: Patients with hepatitis C who underwent THA and TKA had higher rates of infection, aseptic revision surgery, medical complications, and blood transfusion compared with matched control patients. Discussion: Our findings suggest that patients with hepatitis C who undergo THA and TKA are at increased risk of experiencing several postoperative complications, which could mean a substantial increase in the cost of care. Conclusions: Further research is needed to establish quantifiable associations between hepatitis C and postoperative complications among patients with the disease who undergo total joint arthroplasty.